The Impact of Maternal Education on Child Immunization: Evidence from Bangladesh - Md Shahjahan; Giulia La Mattina; Padmaja Ayyagari (Institute of Labor Economics (IZA), 2022)
Vaccine-preventable diseases remain a significant public health concern in Bangladesh. We examine the role of maternal education in improving immunization rates among Bangladeshi children. We exploit the 1994 Female Secondary School Stipend Program (FSSSP), which significantly increased education among rural girls, to identify causal effects. Applying a difference-in-differences model based on differential exposure to FSSSP by birth cohort and rural residence, we find that full immunization rates increased by 5.5 percent among children of mothers eligible for a stipend for 5 years relative to children of mothers who were not eligible, but there were no significant effects for children of mothers eligible for a stipend for only 2 years. Results from event study specifications and placebo tests support a causal interpretation of the impact of maternal education on child immunization.
Keywords: H52; I12; J13; O12; 330; maternal education; school stipend program; child immunization; Bangladesh